Report of the Agricultural Personnel Committee of the Planning Commission - Planning Commission (Planning Commission, 1958)
In the light of the guidance thus furnished by the Committee, the various scientific and technical Advisers of the Ministry of Food and Agriculture prepared papers on the all-India requirements during the Third Plan period in their respective fields of work. These papers were discussed thoroughly at full sessions of the Committee which laid down the lines on which its recommendations were to be drafted. These drafts were prepared in the form of chapters covering each subject under review and further discussed by the Committee. The drafts were forwarded to the State Governments also for their suggestions on the Committee’s approach to the problem.
Planning Commission
Planning Commission